2011
DOI: 10.1111/j.1865-1682.2011.01283.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Emerging Diseases of Fish and Shellfish Using Electronic Sources

Abstract: New and emerging fish and shellfish diseases represent an important constraint to the growth and sustainability of many aquaculture sectors and have also caused substantial economic and environmental impacts in wild stocks. This paper details the results of 8 years of a monitoring programme for emerging aquatic animal diseases reported around the world. The objectives were to track global occurrences and, more specifically, to identify and provide advanced warning of disease threats that may affect wild and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The authors' analysis of data on emerging disease events confirms previous research (21), suggesting that the majority of emerging diseases in finfish and crustacea are viral, whilst most emerging diseases of molluscs are parasites. Most events are caused by the spread of known diseases to new locations, followed by an occurrence in a new host species.…”
Section: Types Of Disease and Drivers For Emergencesupporting
confidence: 73%
See 1 more Smart Citation
“…The authors' analysis of data on emerging disease events confirms previous research (21), suggesting that the majority of emerging diseases in finfish and crustacea are viral, whilst most emerging diseases of molluscs are parasites. Most events are caused by the spread of known diseases to new locations, followed by an occurrence in a new host species.…”
Section: Types Of Disease and Drivers For Emergencesupporting
confidence: 73%
“…The Centre for Environment, Fisheries and Aquaculture Science (Cefas) tracks the global occurrence of emerging diseases in aquatic animals by systematically searching Internet alerting services, newsletters and press coverage, inter alia, for reports of new diseases, new presentations of known pathogens, and known diseases occurring in new geographic locations or new host species (see Thrush et al [21] for a detailed methodology). Tables I, II and III summarise an updated analysis of emerging disease events recorded by the Cefas electronic surveillance programme between 2002 and 2017.…”
Section: Disease Risk Profile Of An Emerging Diseasementioning
confidence: 99%
“…Four literature reviews were included since they provided good knowledge and examples of the use of methodologies for early detection. Specifically, two studies identified patterns of global disease occurrence [137, 138], while the other two reviewed the use of animals as sentinels for bioterrorism [5] or for human disease [139].…”
Section: Resultsmentioning
confidence: 99%
“…However, this is an open area of research, and much work needs to be done (see e.g. Collier et al, 2008;Thrush et al, 2011).…”
Section: Discussionmentioning
confidence: 99%